IKAN-IKAN AIR TAWAR DARI RAWA BANJIRAN SEKITAR SUNGAI TAPUNG MATI KECAMATAN TAPUNG KABUPATEN KAMPAR RIAU - Chaidir P. Pulungan; Neli Safrina (Berkala Perikanan Terubuk, 2014)
Flooded swamp area around the Tapung Mati River is a habitat for many species ofendemic fishes in Riau. A studied to understand the types of freshwater fishes living inthat area has been conducted on June to July 2011. Fish samples were caught used ascoop net (0.5 m diameter) and the fish then identified based on Saanin (1984) danKottelat et al. (1993). In this research, the fish caught were consisted of 20 species thatwere belonged to 3 ordos, 10 families and 17 genus. Most of fish caught were Cyprinid(47,06 %) and the most common species are Esomus metallicus. Around 40 % of fishpresent in the flooded area of the Tapung Mati River are categorized as Sumatra’sprimary family and almost all species are the economically valued fish. African catfishand nile tilapia fishes are aquaculture fishes that escaped from ponds around the river.Keywords:Tapung Mati River, flooded area, freshwater fishes, Esomus metallicus,primary family